2022
DOI: 10.3389/fcvm.2021.639476
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the Notch Signaling Pathway Promotes M2 Macrophage Polarization to Suppress Cardiac Fibrosis Remodeling in Mice With Myocardial Infarction

Abstract: Myocardial infarction (MI) is regarded as a serious ischemic heart disease on a global level. The current study set out to explore the mechanism of the Notch signaling pathway in the regulation of fibrosis remodeling after the occurrence of MI. First, experimental mice were infected with recombination signal binding protein J (RBP-J) shRNA and empty adenovirus vector, followed by the establishment of MI mouse models and detection of cardiac function. After 4 weeks of MI, mice in the sh-RBP-J group were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The different phenotypes of M2 macrophages have different cell surface markers and secrete different cytokines and chemokines. Previous studies have revealed an antifibrotic function by inhibiting TGF-β and increasing M2 macrophages [43,50], which is consistent with our results. Further studies should be designed to explore the different phenotypes of M2 macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…The different phenotypes of M2 macrophages have different cell surface markers and secrete different cytokines and chemokines. Previous studies have revealed an antifibrotic function by inhibiting TGF-β and increasing M2 macrophages [43,50], which is consistent with our results. Further studies should be designed to explore the different phenotypes of M2 macrophages.…”
Section: Discussionsupporting
confidence: 93%
“…Immunofluorescence revealed that SA can increase CD68 + /CD206 + macrophage infiltration by 23%, which suggested that SA can promote the polarization of M2 macrophages. M2 macrophages secrete various antiinflammatory factors and many studies have shown that activation and increase of M2 macrophages can attenuate ventricular remodeling (34)(35)(36)(37). Inhibition or depletion of M2 macrophage inhibiting M2 macrophage activationresulted in deterioration of cardiac function, enlargement of infarct area and increase of inflammatory cell infiltration after MI (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…and Inhibits Angiogenesis after MI. Studies have shown that macrophage polarization affects infarct healing after MI [3]. Flow cytometry was performed to assess macrophage polarization.…”
Section: Macrophage Rmp Deficiency Promotes M1 Polarizationmentioning
confidence: 99%
“…Following infarction, cardiomyocyte death and acute inflammation are induced [2]. Inflammation plays important roles during MI [3,4]. Macrophage polarization is considered to be a major factor that drives the inflammatory process [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation